The Refiguration of Body and Soul: Time and Narrative in C.S. Lewis's Retelling of the Cupid and Psyche Myth - Lukens, Matthew (Amaltea. Revista de Mitocrítica, 2012)
This paper presents a reading of C.S. Lewis’s Till We Have Faces: A Myth Retold in light of Mikhail Bakhtin and Paul Ricoeur’s analysis of time’s role in transformation. I will focus on the narrative dynamics Lewis achieves by incorporating the temporal into the fabric of his narrative. This approach to temporality contrasts markedly with his source material, Apuleius’ Metamorphoses or the Golden Ass, which ultimately appears to transcend time and therefore transformation by novel’s end. I finish my analysis by arguing that as Lewis moves from his protagonist, Orual's, initial retelling to embracing a more limited version of the myth, instead of the disruptive force it is for Apuleius, the temporal becomes a generative force, transforming and renewing Lewis’s narrative along the lines of Ricoeur’s paradigm of prefiguration, configuration, and refiguration.